The process of creating a painting: a case study of contemporary painting exhibition "It’s me" - ฉายะเจริญ สุริยะ (Siam Communication Review, 2016)
The painting was exhibited in contemporary painting exhibition "It’s me" is the creative process that requires the skills of painting with knowledge of the concepts and theories such as inspiration, concept, aesthetics and code. This led to the creation of a clear procedure and can produce a finished painting. This leads to knowledge that can be developed into an academic career in various formats.